2010
DOI: 10.1073/pnas.0913798107
|View full text |Cite
|
Sign up to set email alerts
|

Population robustness arising from cellular heterogeneity

Abstract: Heterogeneity between individual cells is a common feature of dynamic cellular processes, including signaling, transcription, and cell fate; yet the overall tissue level physiological phenotype needs to be carefully controlled to avoid fluctuations. Here we show that in the NF-κB signaling system, the precise timing of a dual-delayed negative feedback motif [involving stochastic transcription of inhibitor κB (IκB)-α and -ε] is optimized to induce heterogeneous timing of NF-κB oscillations between individual ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
210
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(217 citation statements)
references
References 45 publications
3
210
0
Order By: Relevance
“…This suggests that further development of models for cellular communication and propagation of inflammatory signals between cells should be a priority to allow a better understanding of the tissue-level switch between amplification and resolution of inflammation. Recent data (Paszek et al, 2010) has suggested that cell-to-cell heterogeneity is an intrinsic feature of the NF-B system. Therefore, the variability in response to low-dose stimulation might also be a fundamental property of the NF-B inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that further development of models for cellular communication and propagation of inflammatory signals between cells should be a priority to allow a better understanding of the tissue-level switch between amplification and resolution of inflammation. Recent data (Paszek et al, 2010) has suggested that cell-to-cell heterogeneity is an intrinsic feature of the NF-B system. Therefore, the variability in response to low-dose stimulation might also be a fundamental property of the NF-B inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…A model for pulsatile stimulation has been described for the signalling response to NF-κB, whereby a population of cells shows a more efficient response in downstream transcriptional activation to repeated pulses of TNFα stimulation as opposed to a continuous stimulus (Ashall et al, 2009). A broader conclusion from these observations is that the cellular heterogeneity that arises from pulsatile transcriptional responses confers robustness to a cell population (Paszek et al, 2010). In other words, generating enhanced cell heterogeneity at the single-cell level can control the stability of a population of cells by decreasing fluctuations over time at the population level.…”
Section: Pulsatile Transcriptional Activity Can Confer Robustnessmentioning
confidence: 99%
“…In other words, generating enhanced cell heterogeneity at the single-cell level can control the stability of a population of cells by decreasing fluctuations over time at the population level. This might confer an advantage by both preserving the identity of the population and simultaneously enabling the population to respond to signalling stimuli (Paszek et al, 2010). In this scenario, fluctuating gene expression may enable a faster response to signalling.…”
Section: Pulsatile Transcriptional Activity Can Confer Robustnessmentioning
confidence: 99%
“…In response to tonic TNF␣ stimulation, an initial synchronous pulse of NF-B translocation is followed either by nuclear persistence (monophasic activation) or in a minority of cells by dampened oscillatory profiles (22,24). Individual cells producing asynchronous oscillatory responses produce population robustness, a phenomenon that is predicted to reduce tissue sensitivity to paracrine stimuli (26).…”
mentioning
confidence: 99%